2012
DOI: 10.2174/138920312804142110
|View full text |Cite
|
Sign up to set email alerts
|

Functions of MAPR (Membrane-Associated Progesterone Receptor) Family Members As Heme/Steroid-Binding Proteins

Abstract: Progesterone receptor membrane component 1 (PGRMC1), PGRMC2, neudesin, and neuferricin all contain a cytochrome b5-like heme/steroid-binding domain and belong to the membrane-associated progesterone receptor (MAPR) family. Their amino acid sequences are well conserved among vertebrates, from humans to zebrafish. MAPR family genes are abundantly expressed in the central nervous system and exhibit neurotrophic effects in neural cells. During lipid metabolism, PGRMC1 regulates cholesterol synthesis, and neudesin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 69 publications
(130 reference statements)
1
62
0
5
Order By: Relevance
“…In adult mice, neudesin was expressed preferentially in the CNS spinal cord but also in several peripheral tissues (Kimura et al, 2005(Kimura et al, , 2012. NMR studies suggested a similar structure with a potential heme-binding pocket (Han et al, 2012).…”
Section: Neudesinmentioning
confidence: 98%
See 3 more Smart Citations
“…In adult mice, neudesin was expressed preferentially in the CNS spinal cord but also in several peripheral tissues (Kimura et al, 2005(Kimura et al, , 2012. NMR studies suggested a similar structure with a potential heme-binding pocket (Han et al, 2012).…”
Section: Neudesinmentioning
confidence: 98%
“…The four MAPR proteins PGRMC1, PGRMC2, neuferricin and neudesin share a homologous CYB5-like heme/steroidbinding domain but lack homology with the classical nuclear or membrane-bound steroid receptors (Mifsud and Bateman, 2002;Min et al, 2005;Kimura et al, 2012). Recent crystallographic analyses confirmed the hemoprotein nature of PGRMC1 with a special five-coordinated heme iron involving Tyr113, as opposed to the six-coordinated heme with two axial histidines in CYB5 (Min et al, 2005;Kaluka et al, 2015;Kabe et al, 2016).…”
Section: Molecular Biochemical and Cellular Properties Of Maprsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be because Neudesin and Neferricin are present in the luminal compartment and secreted extracellularly (2,3,(24)(25)(26)(27)(28), however the presence of some observed phosphorylation events suggests that the MAPR domain of these proteins may also be found in the cytoplasm. The detection of O-N-acetylgalactosamine (O-GalNAc) glycosylation does not necessarily imply an extracellular location for Neudesin, since 14% of O-GalNAc proteins are annotated with nuclear Gene Ontogeny (GO) assignments (29).…”
Section: Posttranslational Modifications Of Neudesin and Neuferricinmentioning
confidence: 99%